Two new species of Rhabdochona (Nematoda: Rhabdochonidae) from freshwater fishes in Thailand - Moravec, Frantisek; Yooyen, Thanapon (Folia parasitologica, 2011)
Two new species ofrhabdochonid nematodes are described from the intestine of freshwater fishes in Chiang Mai Province, northern Thailand: Rhabdochona (Rhabdochona) pseudomysti sp. n. from the catfish Pseudomystus siamensis (Regan) (Bagridae, Siluriformes) in the Fang Brook, a tributary of the Kok River (the Mekong River basin), Fang District and Rhabdochona (Globochona) thaiensis sp. n. from the cyprinid Mystacoleucus marginatus (Valenciennes) (Cyprinidae, Cypriniformes) in the Ping River (the Chao Phraya River basin), Muang District. Rhabdochona pseudomysti is mainly characterized by simple, leaf-like oval deirids (a unique feature among Rhabdochona spp.), a prostom with 14 anterior teeth, the presence of basal prostomal teeth, the length ratio of the muscular and glandular portions of oesophagus (1:2.1-2.6), an unusually long left spicule (1.10-1.22 mm), length ratio of spicules (1:11.5-14.7), arrangement of genital papillae, and conspicuously elevated vulval lips. Rhabdochona thaiensis differs from other representatives of the subgenus Globochona Moravec, 1972 possessing caudal projections on the tail tip in that it has only 2 claw-shaped projections located ventrally on the tail tip of both males and females; the species is mainly characterized by the presence of distinct pseudolabia, 8 anterior prostomal teeth, absence of basal teeth, bifurcated deirids, length ratio of the muscular and glandular portions of oesophagus (1:11.3-11.9), conspicuously short (135-141 microm) left spicule, arrangement of genital papillae, and somewhat elevated vulval lips. Fully developed eggs of R. pseudomysti and R. thaiensis remain unknown. These are the first nominal species of Rhabdochona reported from Thailand.
Keywords: ženské pohlaví; ryby; Thajsko; Female; Fishes; Animals; Male; hlístice; nematodózy; mužské pohlaví; sladká voda; Nematode Infections; zvířata; nemoci ryb; Fresh Water; Nematoda; Fish Diseases; Thailand